Calcium scores distribution across coronary artery by age and sex: the ImaLife study. (25th November 2020) - Ma, R; Xia, C; Van Assen, M; Vonder, M; Pelgrim, G; Van Bolhuis, J.N; Van Der Harst, P; Vliegenthart, R
Abstract: Background: The distribution of coronary artery calcium (CAC) across the coronary system increases the ability to predict coronary events compared to traditional CAC scoring alone. Reference values for regional distribution of CAC by age and sex are not yet available for a general European population. Purpose: To investigate the distribution of CAC across the coronary arteries by age and sex in the population-based ImaLife study. Methods: ImaLife is part of Lifelines, a multi-generational, prospective cohort study with over 167, 000 participants from the northern Netherlands. From 2017–2019, 5, 531 participants aged 45–84 years underwent non-contrast cardiac CT using third-generation dual-source CT. Total and vessel-specific CAC scores (Agatston's method) were acquired semi-automatically using dedicated software. Participants with a positive CAC score were classified into three groups: total CAC score 1–100, 101–300 and >300. The diffusivity index (equation: 1 – [highest one-vessel CAC/total CAC]) was calculated. The diffusivity index is an expression of the relative distribution of CAC across the coronary arteries. Data were analyzed for the whole population and by sex and age groups. Mann-Whitney U test was used to analyze the diffusity index in men and women. Kruskal-Wallis H tests were performed to test the diffusivity index in different age groups. Results: In total 2, 376 men (mean age 56.4±7.7 years) and 3, 155 women (mean age 56.0±7.5 years) were analyzed. In participants with CAC, 1, 2, 3 or 4 vessels were affected in 523 (22.0%), 560 (17.7%), 371 (15.6%) and 257 (8.1%) of men, respectively, and in 385 (16.2%), 175 (5.5%), 185 (7.8%) and 81 (2.6%) of women, respectively (P<0.001). The number of 1, 2, 3 or 4 vessels affected were significantly different by age (p<0.001). In age category 45–49 years, CAC in 1, 2, 3, and 4 vessels was present in 60.1%, 21.6%, 15.5%, and 2.9%, respectively; for age 74+ years, these percentages were 19.3%, 19.3%, 31.1% and 30.3%, respectively. The number of affected vessels were significantly different in different CAC categories (p<0.001), see Figure. More vessels were affected in higher CAC categories. The median diffusivity index was higher in men than in women (0.10 (IQR: 0–0.36) vs 0 (IQR: 0–0.24), p<0.001) and increased by increasing age. For age categories of 45–49, 50–54, 55–59, 60–64, 65–69, 70–74, and >74 years, diffusivity indexs were 0 (IQR: 0–0.12), 0 (IQR: 0–0.22), 0.02 (IQR: 0–0.28), 0.10 (IQR: 0–0.35), 0.16 (IQR: 0–0.42), 0.20 (IQR: 0–0.44), and 0.28 (IQR: 0.03–0.45) (p<0.001). Conclusions: In this Dutch population-based study, male participants had higher prevalence of CAC with higher number of involved vessels, and a higher diffusivity index compared to women. For both sexes, involved vessels and diffusivity index increased with age. The reference values of this regional distribution of CAC in a European population can assist in risk categorization of cardiovascular events. Funding Acknowledgement: Type of funding source: Other. Main funding source(s): Siemens Healthineers